Penerapan Metode ELECTRE dalam Menentukan Penerima Penghargaan Adiwiyata - Fince Tinus Waruwu; Mesran Mesran; Hotmoko Tumanggor (STMIK Budi Darma, 2022)
Adiwiyata is one of the Ministry of Environment's programs within a framework supported by school knowledge and awareness in environmental preservation and sustainable development efforts. Therefore, appreciation is needed for Adiwiyata schools in order to provide motivation and improve performance. The determination of the North Sumatra adiwiyata award recipient still uses a manual system and requires quite a long time. Based on these problems, we need a system that supports the decision (SPK) that allows you to receive recipients of adiwiyata awards using existing criteria. One method that can be used is Elimination Et Choix Traduisant la Realite (ELECTRE). This method can solve the type of problem in making decisions with alternatives and criteria that have been given the weight of research using ELECTRE to produce the lowest ranking ranking or highest ranking. The results showed that A4 was the best